THE EFFECT OF PAIRED READING STRATEGY IN READING STUDENTS’ ACHIEVEMENT - Surti Milarisa; Penti Hevina Dewi (Universitas Islam Ogan Komering Ilir Kayuagung, 2019)
The aimof the study wasto find out the effect of paired readingstrategy in readingstudents’ achievement of the Eighth Grade Students ofSMPN 1 TelukBayur.The design of this research was quantitativedesign. The subject of the research was the eighth grade students of SMPN 1 TelukBayur. By using purposive sampling, the researchers found a sample in this research. The sample of the research was class VIII Chaving31students which consistedof 17female and 14male students. Reading test in the form of multiple-choice which consisted of 20 questions was used to collect the data. To analyze the data, the researcher applied formula paired sample t-test.Based on the result of paired samples test, the mean scorewas 8.064 , standard error was 1.325, the value of tobtainedwas 6.084, at the significance level of p<0.05 in two-tailed testing and df=30. Since the value of tobtained (6.084) was higher than ttable (2.0423) and pvalue (0.00) was less than αvalue (0.05), it meant that a paired reading strategy helped students learn easily to understand the content of the text